Molecular Detection Methods in HPV-Related Cancers - Williams, Jordana; Kostiuk, Morris; Biron, Vincent L. (Frontiers in Oncology, 2022)
Human Papillomavirus (HPV) is responsible for most cervical cancers and some head and neck cancers, including oropharyngeal squamous cell carcinoma (OPSCC) and HPV-related multiphenotypic sinonasal carcinoma (HMSC). Cervical cancer is commonly diagnosed by liquid-based cytology followed by HPV testing using commercially available DNA polymerase chain reaction (PCR), p16 immunohistochemistry (IHC), or DNA/RNA in-situ hybridization (ISH). HPV in head and neck cancers is commonly diagnosed by p16 immunohistochemistry (IHC) or by RT-qPCR of HPV-16 E6 and E7 oncoproteins. Droplet digital PCR (ddPCR) has been reported as an ultrasensitive and highly precise method of nucleic acid quantification for biomarker analysis and has been used to detect oncogenic HPV in oropharyngeal and cervical cancers.